The Trends of Urolithiasis Therapeutic Interventions over the Last 20 Years: A Bibliographic Study - Abedi, Amir Reza; Razzaghi, Mohammadreza; Montazeri, Saeed; Allameh, Farzad (Journal of Lasers in Medical Sciences, 2021)
Introduction: The clinical and economic burden of kidney stones is a challenge for the healthcare system. There is a limited bibliometric project exploring the literature trends on ‘urolithiasis’ and its related management. Methods: A review was conducted to discover the related abstracts regarding each specific issue, investigated year by year from May 2000 to May 2020. To make an effective comparison, the statistics resulting from every single study were allocated to two 10-year periods: period 1 (2000 to 2010) and period 2 (2010 to 2020). We included all English language articles, all non-English articles with English abstracts, and studies in which interventions were used for stone removal, including laser technology. Results: These articles are about ureteroscopy (URS) (n=10360, 33.45%), percutaneous nephrolithotomy (PCN) (n =10790, 34.84%) and extracorporeal shockwave lithotripsy (ESWL) (n=9846, 31.76%). When evaluating the two time periods, there were 9912 studies available in period one, which increased by ×2.12 times (112.71% rise) to 21 084 studies in period two (P=0.001). The increase was 133%, 103.51%, and 70.4% for URS, PCN, and SWL respectively. A total of 855 studies on Laser application via URS were published on PubMed over a 20-year period. There was an increasing trend toward using laser applications via URS over the study period. Also, there were 230 articles published in period one, which increased by nearly 2.71 times to 625 papers in period two (P< 0.001). There was an increasing trend toward using laser application via PCN; 126 papers were published in period one, which increased by nearly 3.05 times (rise of 205.5%) to 385 papers in period two (P = 0.002). Conclusion: The minimal invasive interventions for stone removal, including URS and PCN, increased dramatically in the last decade, and the use of lasers in stone treatment increased significantly in the last decade. DOI:10.34172/jlms.2021.14